(Ni, Co)Se2 nanoparticles on vertical graphene nanosheets@carbon microtubes for high-performance solid-state asymmetric supercapacitors. (September 2022) - Yin, Xuemin; Han, Liyuan; Fu, Yanqin; Lu, Jinhua; Song, Qiang; Li, Hejun
Abstract: Much attention has been draw to transitional metal selenides (TMSe) for energy storage, especially the high-performance supercapacitor devices, so it is research hotspots to construct free-standing electrode with TMSe loading. In this work, 3D carbon microtubes (CMTs) wrapped by vertical graphene nanosheets (VGNs), were fabricated by plasma-enhanced chemical vapor deposition (PECVD) method using SiO2 nanowires as templates, which were served as free-standing, conductive and flexible substrates for supporting (Ni, Co)Se2 nanoparticles. Benefiting from the structural merits, such as the interwoven CMTs network, high conductive VGNs substrate, and the synergistical effect of nanostructured (Ni, Co)Se2, the fabricated CMTs@VGNs@(Ni, Co)Se2 membrane electrode exhibits excellent electrochemical performance in terms of high specific capacitance (1740 F g −1 at 1 A g −1 ), good rate capability (71.8 % capacitance retention at 20 A g −1 ), and superior cycling stability (89.6 % capacitance retention after 10, 000 cycles). Notably, the solid-state asymmetric supercapacitor (ASC) assembled with CMTs@VGNs@(Ni, Co)Se2 membrane and activated carbon (AC), not only delivers a high energy density of 41.6 Wh kg −1 at a power density of 0.75 kW kg −1, but also shows long cycle life with excellent performance stability. More impressively, our work provides a new idea for structural construction of 3D carbon-based nano-substrates and self-supporting electrodes for supercapacitors. Graphical abstract: Unlabelled Image Highlights: Hierarchical core-shell CMTs@VGNs were prepared as substrates by PECVD method using SiO2 nanowires as templates. The CMTs@VGNs@(Ni, Co)Se2 membrane electrode exhibits excellent electrochemical performance. The asymmetric supercapacitor shows high good energy density and long cycle life.